Parallel nonlinear optimization techniques for training neural networks - Phua, P.K.H.; Daohua Ming (IEEE transactions on neural networks, 2003)
In this paper, we propose the use of parallel quasi-Newton (QN) optimization techniques to improve the rate of convergence of the training process for neural networks. The parallel algorithms are developed by using the self-scaling quasi-Newton (SSQN) methods. At the beginning of each iteration, a set of parallel search directions is generated. Each of these directions is selectively chosen from a representative class of QN methods. Inexact line searches are then carried out to estimate the minimum point along each search direction. The proposed parallel algorithms are tested over a set of nine benchmark problems. Computational results show that the proposed algorithms outperform other existing methods, which are evaluated over the same set of test problems.